Magical and Popular Veterinary Uses of Rue (Ruta L., Rutaceae) by Shepherds in Eastern Spain - Vidal-González, Pablo; Sánchez-Padilla, Raquel (Ethnobotany Research and Applications, 2015)
Rue is a plant of Mediterranean origin which is widely used by shepherds to protect the sheep. Ruta chalepensis L. and Ruta angustifolia Pers. are the species studied in this context. This article documents the popular veterinary uses of rue as well as the importance this plant has in the shepherd world as a protector against witches, evil eye, and other evils, underscoring the protection strategies employed to fight these evils that have so concerned caregivers of herds. Semi-structured interviews of veteran shepherds are the basis of this paper. Resumen La ruda es una planta de origen mediterráneo muy utilizada por los pastores de ganado lanar para proteger a las ovejas. Ruta chalepensis L. and Ruta angustifolia Pers. son las especies estudiadas en este contexto. Este artículo recoge los usos veterinarios tradicionales de la ruda, pero sobre todo la importancia que esta planta tiene en el mundo pastoril como protectora contra brujas, el mal de ojo y otros males, subrayando las estrategias de protección empleadas para combatir estos males que tanto han preocupado a los cuidadores de los rebaños. Entrevistas semi-estructuradas a pastores veteranos son la base de esta investigación.